2013
DOI: 10.1007/s00122-013-2125-6
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping of powdery mildew resistance in WI 2757 cucumber (Cucumis sativus L.)

Abstract: Powdery mildew (PM) is a very important disease of cucumber (Cucumis sativus L.). Resistant cultivars have been deployed in production for a long time, but the genetic mechanisms of PM resistance in cucumber are not well understood. A 3-year QTL mapping study of PM resistance was conducted with 132 F2:3 families derived from two cucumber inbred lines WI 2757 (resistant) and True Lemon (susceptible). A genetic map covering 610.4 cM in seven linkage groups was developed with 240 SSR marker loci. Multiple QTL map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 24 publications
3
67
1
Order By: Relevance
“…However, Shanmugasundarum et al (1971) differentiated between hypocotyl and leaf resistance and concluded that a recessive gene for hypocotyl resistance (pm-h) is essential for overall resistance. He et al (2013) and Walters et al (2001) also showed that a single-recessive gene (pm-h) controls hypocotyl resistance, and the role of a single gene in resistance is supported by other studies (Zhang et al, 2004;Liu et al, 2008a). By contrast, some studies reported that resistance is controlled by a pair of incomplete recessive genes and two pairs of epistatic genes (Shanmugasundarum et al, 1971;Mao et al, 2005).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…However, Shanmugasundarum et al (1971) differentiated between hypocotyl and leaf resistance and concluded that a recessive gene for hypocotyl resistance (pm-h) is essential for overall resistance. He et al (2013) and Walters et al (2001) also showed that a single-recessive gene (pm-h) controls hypocotyl resistance, and the role of a single gene in resistance is supported by other studies (Zhang et al, 2004;Liu et al, 2008a). By contrast, some studies reported that resistance is controlled by a pair of incomplete recessive genes and two pairs of epistatic genes (Shanmugasundarum et al, 1971;Mao et al, 2005).…”
Section: Introductionmentioning
confidence: 81%
“…The new primers and 10 pairs of SSR primers published by He et al (2013) were first used to screen for polymorphisms in the parents. Then, selected primers were used in the F 2 population to determine whether or not they were linked to the pm-s gene.…”
Section: Development Of New Molecular Markers and Second Mapping Of Tmentioning
confidence: 99%
See 3 more Smart Citations